Conceptualizing myocardial contractility as an emergent property that characterizes myocardial contraction - Kuang, Serena Y.; Geloian, Gorune (Frontiers in Physiology, 2025)
Myocardial contractility (MC) is a fundamental concept that is widely used to describe the cardiac muscles’ mechanical function, yet its definitions in textbooks and literature are vague, inconsistent, and often contradictory. In this article, we categorize these many issues into five groups and conducts a conceptual analysis to redefine MC from a broader, more comprehensive perspective. We propose a functional, three-domain framework of MC consisting of capacity/resource, adaptability, and ability (force (F) and/or velocity (V) generated during muscle contraction), emphasizing the dynamic, non-linear interactions among the three domains and their clinical significance. Specifically, we highlight how interventions targeting MC may produce non-linear effects, suggesting a shift toward optimizing resource use rather than maximizing outputs (i.e., F and/or V of myocardial contraction, the outputs of the ability domain), which could potentially reduce the complications of positive inotropic interventions. We also discuss the implications of several new conceptual developments as the byproducts of the three-domain MC framework. Additionally, we identify system-level emergent properties of MC briefly, including contraction efficiency, circadian rhythm-dependence, temperature-dependence, and history-dependence, with implications for cardiac muscle research, exercise training, and clinical decision-making. The three-domain functional framework of MC resolves the inconsistencies in definitions, differentiates MC from cardiac performance, and offers a structured perspective for facilitating both experimental studies and therapeutic strategies.